Mexico’s Middle Power Politics through MIKTA Coalition Strategy for Influence in Unequal Global Governance - Oscar Rodrigo Victoria Velasco (UIN Sunan Gunung Djati, 2026)
Global governance is increasingly shaped by major power groupings such as the G7, BRICS, and the G20. This structure creates political constraints for middle powers that have diplomatic capacity but limited individual influence in global decision-making. This study examines how Mexico uses Mexico, Indonesia, Korea, Turkey, and Australia (MIKTA) as a coalition strategy to strengthen its political influence in global governance. The study uses a qualitative case study design based on desk research. The analysis relies on official documents, MIKTA statements, government publications, and academic literature on middle powers, role theory, and Mexico’s foreign policy. Role theory is used to examine Mexico’s agenda-setting, coalition-building, niche diplomacy, institutional engagement, leadership role, and recognition-seeking. Data are analyzed through source triangulation and thematic interpretation to ensure consistency between diplomatic discourse and political role performance. The study finds that Mexico uses MIKTA to expand diplomatic visibility, strengthen coalition-based bargaining, and seek recognition as a global governance actor. Mexico’s middle power activism through MIKTA shows that influence is not only produced through material power, but also through role performance, institutional engagement, and coalition politics. This study contributes to political science debates on middle power activism, coalition politics, and the role of secondary powers in unequal global governance structures.